MTHFR C677T、MTHFR A1298C、MTRR A66G and MTR A2756G polymorphisms and male infertility risk: a systematic review and meta-analysis - Feng Li; Ju-ju Qi; Li-xin Li; Teng-fei Yan (BMC, 2024)
Abstract Background Epidemiological studies have reported that polymorphisms of folate-metabolizing genes have a significant impact on male infertility. However, the results of published studies have come to different conclusions. Objective To determine an association between folate-metabolizing gene polymorphisms and the risk of male infertility. Methods The meta-analysis was conducted according to the PRISMA 2020 statement. The protocol was registered with PROSPERO (CRD42023412251). Studies were searched from PubMed, Google Scholar, Embase, Scopus, and the Cochrane Library up to 24st October2023. Articles that satisfied the inclusion criteria were evaluated for their quality using the Newcastle-Ottawa Scale. Data were extracted from the eligible studies and were analyzed for pooled up odds ratio (OR) with 95% confidence interval (CI). Meta-analysis was conducted using STATA 12. Results Forty-six case-control studies were included in the meta-analysis which comprised 20,639 participants. The pooled analysis revealed that the MTHFR C677T polymorphism was significantly associated with male infertility and abnormospermia.Three-fifths of the model showed there was a significant association between the MTR A2756G polymorphism and male infertility. Both MTHFR A1298C and MTRR A66G polymorphisms were not significantly associated with male fertility. Furthermore, subgroup analysis revealed a significant association between the MTHFR C677T polymorphism and male fertility in Asian countries. Conclusion This meta-analysis suggests that the MTHFR C677T and MTR A2756G polymorphisms may be a potential risk factor for male infertility.